2023
DOI: 10.7554/elife.84630
|View full text |Cite
|
Sign up to set email alerts
|

Cortico-thalamo-cortical interactions modulate electrically evoked EEG responses in mice

Abstract: Perturbational complexity analysis predicts the presence of consciousness in volunteers and patients by stimulating the brain with brief pulses, recording electroencephalographic (EEG) responses, and computing their spatiotemporal complexity. We examined the underlying neural circuits in mice by directly stimulating cortex while recording with EEG and Neuropixels probes during wakefulness and isoflurane anesthesia. When mice are awake, stimulation of deep cortical layers reliably evokes locally a brief pulse o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 109 publications
1
21
0
Order By: Relevance
“…Conversely, the long‐lasting, phase‐locked responses that we observed in layers 6, 5 and 1 match more closely the input from thalamic matrix and intralaminar nuclei (Harris et al, 2019) and may even directly reflect synaptic input from these nuclei, which contribute to cortical arousal in humans (Schiff et al, 2007), monkeys (Bastos et al, 2021; Redinbaugh et al, 2020) and rats (Xu et al, 2020). Indeed, a recent study suggested that long‐lasting EEG responses following cortical stimulation are sustained through cortico–thalamo–cortical interactions in wake but not anesthetized mice (Claar et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the long‐lasting, phase‐locked responses that we observed in layers 6, 5 and 1 match more closely the input from thalamic matrix and intralaminar nuclei (Harris et al, 2019) and may even directly reflect synaptic input from these nuclei, which contribute to cortical arousal in humans (Schiff et al, 2007), monkeys (Bastos et al, 2021; Redinbaugh et al, 2020) and rats (Xu et al, 2020). Indeed, a recent study suggested that long‐lasting EEG responses following cortical stimulation are sustained through cortico–thalamo–cortical interactions in wake but not anesthetized mice (Claar et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, when consciousness is lost or strongly reduced, for example, in slow‐wave sleep or anaesthesia, the cortical responses are short‐lasting and stereotypic, resulting in low PCI values (Casali et al, 2013; Massimini et al, 2005). Similarly, recent experiments in rats and mice have shown that general anaesthesia and deep sleep reduce PCI and global functional connectivity following electrical stimulation in vivo (Arena et al, 2021, 2022; Cavelli et al, 2023; Claar et al, 2023). In vitro studies in cortical slices showed that the application of noradrenaline and a cholinergic agonist increased the PCI (D'Andola et al, 2018), whereas GABA antagonists reduced PCI (Barbero‐Castillo et al, 2021).…”
Section: Introductionmentioning
confidence: 86%
“…The principal brain structure that drives brain state changes during sleep, including our measurement of them with EEG, is the corticothalamic system [28][29][30]. Different stages of sleep have been linked to changes in corticothalamic activity [29,[31][32][33][34] and to changes in the periodic and aperiodic components of the EEG signals over those changes [35,36,34,37]. For instance, the transition from wakefulness to N1 sleep is also characterized by an increase in the slope of the 1/f component and the low-frequency band powers [35,36], which is itself observed to be associated with corticothalamic communication [30].…”
Section: Introduction Sleep Neurophysiology and Eegmentioning
confidence: 99%
“…The neuronal excitation spreads along the stimulated axons and causes secondary activations of connected neuronal populations generating later components of the EPs. These late responses have been ascribed to recurrent interactions across cortical areas 17 , cortico-thalamo-cortical loops 18,19 and in the case of non-invasive stimulation to somatosensory and auditory confounds due to the activation of somatosensory and auditory receptors 20 . Brain areas generating scalp EPs can be coarsely identified using parameter-dependent source reconstruction methods 2125 ; however, the relationship between EP components and the spiking activity of the underlying neuronal populations is far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…A multiscale approach that combines EEG, local currents, and single neurons’ recordings is therefore important to identify the origin of the late EP component. The neuronal mechanisms generating local field potentials ( LFPs ) have been explored in classical studies 2628 , but only few studies have combined and linked LFP, EEG and units’ activity 18,29,29 . We previously inferred that cortico-thalamo-cortical interactions drive the long-lasting EPs 18 , however we did not causally link the contribution of the thalamus to a specific EP component.…”
Section: Introductionmentioning
confidence: 99%